Kinship terminology in the Tamiang language: A Malay variety spoken in Eastern Aceh, Indonesia - Zulfadli A. Aziz; Maya Safhida; Masrizal Mahmud (Universitas Syiah Kuala, 2020)
This qualitative research examines kinship terms in the Tamiang language and the strategies of selection of the terms by its speakers. The data for this research were obtained through questionnaire, and interview from eight informants living in Bendahara Sub-District, Kejuruan Muda Sub-District, Karang Baru Sub-District, and Seruway Sub-District, Aceh Tamiang Regency, the Aceh Province. Observation was also done on the use of some of the kinship terms directly by the people in the speech community. This observation took place while the authors were socializing with the speakers in the research location. The results showed that the kinship terms in the Tamiang language are based on consanguinity and affinity. The kinship terms in the language also refer to birth order. Then, the strategies of the selection of kinship terms in the Tamiang language are based on kinship, age, gender, and descent, especially in terms of a speech event. Viewed role relationships, the terms addressed to men/women in the third layer of vertical relationships are not different. The horizontal relationship indicating the position of siblings and wife/husband is equal. The horizontal role relationship of cousins in the Tamiang language is limited to the third order. This study is very urgent since the study on kinship terms in the Tamiang language has not been conducted comprehensively before. Complete terms used to address family members in the Tamiang language are provided in this study, and it can be one of the resources for further research in the same field of study.